Cloud and fog computing platforms for Internet of Things - Bhambri, Pankaj; Rani, Sita; Gupta, Gaurav (Computer science professor); Khang, Alex ([Place of publication not identified] : Chapman and Hall/CRC, 2022)
Today, relevant data are typically delivered to cloud-based servers for storing and analysis in order to extract key features and enable enhanced applications beyond the basic transmission of raw data and to realize the possibilities associated with the impending Internet of Things (IoT). To allow for quicker, more efficient, and expanded privacy-preserving services, a new trend called Fog Computing has emerged: moving these responsibilities to the network's edge. Traditional centralized cloud computing paradigms confront new problems posed by IoT application growth, including high latency, limited storage, and outages due to a lack of available resources. Fog Computing puts the cloud and IoT devices closer together to address these issues. Instead of sending IoT data to the cloud, the fog processes and stores it locally at IoT devices. Unlike the cloud, fog-based services have a faster reaction time and better quality overall. Fog Computing, Cloud Computing, and their connectivity with the IoT are discussed in this book, with an emphasis on the advantages and implementation issues. It also explores the various architectures and appropriate IoT applications. Fog Computing, Cloud Computing, and Internet of Things are being suggested as potential research directions. Features: A systematic overview of the state-of-the-art in Cloud Computing, Fog Computing, and Internet of Things Recent research results and some pointers to future advancements in architectures and methodologies Detailed examples from clinical studies using several different data sets
1. Resource Allocation Techniques in Cloud ComputingKrishna Sowjanya K. and S.K. Mouleeswaran 2. Transforming Healthcare through Internet of ThingsDhanabalan Thangam, Anil B. Malali, Gopalakrishnan Subramanian, and Jin Yong Park3. IoT Motivated Cyber-Physical and Industrial Internet SystemsSaurabh Kumar and Nainsi Soni4. Internet of Things in E-commerce: A Thematic AnalysisPrateek Kalia5. Data Security and Privacy in Fog Computing ApplicationsNazeer Haider and Chandrashekhar Azad6. Energy-Efficient Cloud and Fog Computing in Internet of Things: Techniques and ChallengesAvita Katal and Vitesh Sethi7. Deployment of Distributed Clustering Approach in WSNs and IoTsRachna, Yogesh Chhabra, and Pankaj Bhambri8. Long Range IoT for Agricultural Acquisition through Cloud ComputingKalpana Murugan and Jenitha. R9. Resource Allocation with Task Scheduling in Cloud ComputingRanjan Kumar Mondal, Enakshmi Nandi, Payel Ray, and Debabrata Sarddar10. Service Availability of Virtual Machines in Cloud ComputingOpeyemi Osanaiye and Steve Adeshina11. Analysis of Security Challenges and Threats in Social Network and Cloud ComputingBindu Madavi K.P., P. Vijayakarthik12. Secured Trusted Authentication With Trust Based Congestion Scheme for V2V CommunicationJithendra H.N. and Rekha D.13. MQTT Protocol-based Wide Range Smart Motor Control for Unmanned Electric Vehicular Application: A Case Study in IoTArunava Chatterjee and Biswarup Ganguly14. IoT-based Water Quality Monitoring System using Cloud for Agriculture UseDhanalakshmi R., Jose Anand, Arun Kumar Sivaraman, and Sita Rani
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Cloud computing; COMPUTERS -- Information Technology; COMPUTERS -- Computer Engineering